FeS₂/ZnO core/shell nanowires: structural, optical and electrochemical properties. - Retana Betancourt, María Fernanda (2016)
Purpose and Study Method: Photovoltaic devices with high efficiencies is a top issue due to the importance of alternative systems for energy generation. Altough, many efforts have been done in order to find the characteristics and properties that allow the subsequent production and commercialization, hybrid solar cells represent an interesting option for this purpose. The composition in the photoactive layer is key in order to obtain high values of efficiencies and where the use of nanosized materials with one-dimensional morphology embedded into polymeric matrix allows the improvement of their optoelectronic properties. Thus, it is the aim of this thesis the synthesis of core/Shell nanowires and the coupling with a conductive polymer. Materials synthesized in this thesis were FeS2 (pyrite), ZnO and a polyselenophene. In order to generate onedimensional materials, AAO templates were used for this purpose and an alternative polymerization method, as aldol condensation was carried out. Contributions and Conclusions: ZnO and FeS2 were obtained by immersion method of AAO templates and by microwave heating method respectively. Optoelectronic properties of ZnO nanotubes were study in order to fill them with FeS2 (pyrite). FeS2 (pyrite) was carried out by the study of its mechanism, conditions of temperature, iron and sulfur source, reaction time among others. Core/shell nanowires of FeS2/ZnO were obtained through AAO template-assisted method and exhibit structural, optoelectronic and morphological properties for its potential application in the photoactive layer of hybrid solar cells. Besides, a polyselenophene was obtained through aldol condensation using non-toxic reagents. The conducting polymer exhibit absorption in visible range and charge transfer due to different interactions